(untitled) (Italian Journal of Public Health, 2007)
Background: Population based screening for cardiovascular disease risk factors can potentially reduce coronary heart disease mortality and morbidity. There is little contemporary evidence that has examined the actual impact of such a programme on population health and on reducing inequality in health between affluent and deprived areas. Methods: 82,015 residents of Stockport Health Authority, UK age 35-60 took up an invitation to be screened for cardiovascular disease risk factors from 1989 -1999. We compared uptake of screening and coronary heart disease (CHD) mortality and hospital admissions (1997 – 2003) between screened and unscreened male and female populations from affluent and deprived areas. Results: Males and females in the unscreened population were more likely to die from CHD (IRR=3.60; p<0.001, IRR=4.64, p<0.001) and to have a hospital episode (IRR=1.75, p<0.001, IRR=1.94, p<0.001) than those in the screened population. This was independent of age and deprivation. The highest rates of CHD mortality and hospital admissions were found for unscreened deprived populations, the lowest for screened affluent populations. For both males and females mean rates of CHD mortality and hospital admissions were significantly lower for those who were screened and living in deprived areas compared to those who were unscreened and living in affluent areas. Conclusions: Screening for cardiovascular disease risk factors improved the cardiovascular health of the population by targeting and treating ‘high risk’ groups, including those living in deprived areas. The potential of screening to reduce health inequality by promoting faster and more substantial health improvement in deprived areas was not observed in this study.